Pengaruh Promosi Jabatan Dan Mutasi Terhadap Prestasi Kerja Pegawai PT. Bank Mandiri (Persero) Cabang Ahmad Yani Medan - Suria Alamsyah Putra (Information Technology and Science (ITScience), 2021)
The company is a form of formal organization and is a container where the system of cooperation made in carrying out various activities to achieve organizational goals and objectives expected. The expected goals and objectives can be achieved in general is getting a fair profit, growth and ensuring the survival of the company itself, where employees generally tend towards the work at the desired level of performance the company, if the employee has received a satisfaction in working according to level of need. The Importance of Position and Movement Promotion application based on the principle of fairness and objectivity in the company's employees have been interested to see how the actual role of Promotions Position and Movement applied to the company's employees to achieve a high level of achievement.The problem in this research aims to identify and measure explicitly the influence of Position and Movement Promotion of Job Performance in PT. PlN (Persero) Branch Medan North Sumatra Medan Rayon South.This study aims to determine and measure explicitly the influence of Position and Movement Promotion of Job Performance employees. This study used a questionnaire that is used as a tool to get the primary data (quantitative) with Likert-scale system that was distributed to 72 respondents. The data then compiled in the tables showing the frequency and percentage values ??of each respondent's answer, then processed and analyzed using multiple regression, and processed with the help of the program Statistical Product and Service Solution (SPSS version 18.00) . Retrieved calculation Position and Movement Promotion simultaneously and significantly affect the level confidence Job Performance 29% or 5% significant level according to the results of 15.484 Fcount > Ftable of 2.74 with significance level 0.00 <0.05. Thus far below the 0.05 probability then reject H0 (Accept H1.) Partially an effect of Position of Job Performance Promotions, which is seen from tcount of 5.418> ttable amounted to 1.667 and 0.00 significant probability value < 0.05 then concluded Reject H0 (Accept H1.) For the most dominant variable is the variable Position Promotions seen from Table 4.38 Standaridizied value the importance of the largest beta coefficient of the variable under study is equal to 0.552, while the mutation is only worth 0.024, it can be concluded that the dominant influence Promotion Position Job Performance PT.PLN employees (Persero ) Rayon Medan North Sumatra Medan branch of the South, it means that hypothesis 1 and hypothesis 2 acceptable.